Penerapan Standar Akuntansi Keuangan Entitas Mikro Kecil Menengah Pada Usaha Budidaya Lele Pak Kasanun - Cicik Sarani (Universitas Islam Nahdlatul Ulama Jepara, 2023)
Pak Kasanun's catfish farming business is located in the subdistrict of Akun, Kepanjenkidul District, Blitar City. This business has been running since 1997. Financial management in a business is the main problem in the development of MSMEs. Simple accounting is still used by many MSMEs. Financial reports that refer to standards are still not understood by MSME players. Looking at the company's financial condition, knowledge of financial reporting is very important. On January 1 2018, a new accounting standard was issued, especially for MSMEs, namely FAS MSMEs (Financial Accounting Standards for Micro, Small and Medium Entities). Accounting standards are published by the Accounting Standards Board. This research aims to enable MSME players to prepare financial reports correctly and in accordance with standards. Financial reports that comply with standards can be used by business owners to evaluate business performance, attract investors, and so on. The descriptive qualitative method is used by researchers to conduct this research. The researchers conducted interviews and observations at the research field, then the data obtained by the researchers was processed and financial reports were prepared by referring to FAS MSMEs. In the research process, the researchers encountered obstacles that caused business actors not to carry out records in accordance with FAS MSMEs.